Describing Gambling Affinity: The Role of Personality Traits - John Grable; So-Hyun Joo; Eun Jin Kwak (Journal of Financial Therapy, 2021)
This study was undertaken to determine the degree to which personality dimensions provide insights into who is likely to gamble a significant dollar amount at a casino. Using measures of the Big Five, respondents were grouped into one of the following four personality clusters: (a) Moderate Trait Scores, in which no trait dimension was dominant; (b) Elevated Trait Scores, where a respondent scored highly across trait dimensions; (c) Agreeably Conscientious, in which a respondent scored highly on the agreeableness and conscientious trait domains; and (d) Highly Extraverted, where a respondent’s dominant trait dimension was extraversion. Respondents who were classified as Highly Extraverted were the most likely to gamble a day’s wages at a casino. Those classified into the Moderate Trait Scores cluster also exhibited a gambling affinity. Other factors associated with gambling affinity included subjective financial knowledge, financial satisfaction, and risk tolerance. Results from this study show that personality traits are important descriptors of gambling affinity; however, rather than there being a direct relationship with individual trait factors, the willingness to gamble appears to be based on unique combinations of personality. Findings from this study provide direct insights into who is more likely to require financial advice regarding gambling expenditures at the household level.
Keywords: gambling; personality; risk taking; gambling affinity